2021
DOI: 10.3390/plants10020350
|View full text |Cite
|
Sign up to set email alerts
|

Response of Olive Shoots to Salinity Stress Suggests the Involvement of Sulfur Metabolism

Abstract: Global warming has two dangerous global consequences for agriculture: drought, due to water scarcity, and salinization, due to the prolonged use of water containing high concentrations of salts. Since the global climate is projected to continue to change over this century and beyond, choosing salt-tolerant plants could represent a potential paramount last resort for exploiting the secondary saline soils. Olive is considered moderately resistant to soil salinity as compared to other fruit trees, and in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
4
17
0
Order By: Relevance
“…The same results were observed in soybean plants with overexpression of the tobacco osmotin gene [208]. Bashir et al found that improving salt tolerance by overexpressing tobacco osmotin protein in Olive has something to do with the sulfur metabolism of the transgenic plants [209,210]. Though we have found some evidence for the role of tobacco osmotin protein in enhancing plant stress resistance, the complete mechanism of osmotin activity has not been fully elucidated, and is waiting to be revealed.…”
Section: Genetic Improvement Techniquessupporting
confidence: 73%
“…The same results were observed in soybean plants with overexpression of the tobacco osmotin gene [208]. Bashir et al found that improving salt tolerance by overexpressing tobacco osmotin protein in Olive has something to do with the sulfur metabolism of the transgenic plants [209,210]. Though we have found some evidence for the role of tobacco osmotin protein in enhancing plant stress resistance, the complete mechanism of osmotin activity has not been fully elucidated, and is waiting to be revealed.…”
Section: Genetic Improvement Techniquessupporting
confidence: 73%
“…In this study, moderate and severe salt stresses remarkably reduced the contents of photosynthetic pigments in a concentration‐dependent manner (Figure 2A). Likewise, long‐term exposure to salinity showed a typical negative effect, such as decreased Chl contents in different olive genotypes (Bashir et al 2021). In contrast, MEL application maintained Chl a , Chl b , total Chls, and CARs in the leaves of olive seedlings grown under moderate and severe salt stresses (Figure 2A), implying that MEL might participate in the biosynthesis and/or protection of Chls and CARs, thereby contributing to sustaining the photosynthetic process during salt stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, transgenic C. annum plants showed increased proline, chlorophyll, relative water contents, and antioxidative enzymes (Subramanyam et al, 2011). In a recent report, Bashir et al (2021) demonstrated salt tolerance in transgenic olive (Olea europaea L.) plants over-expressing the tobacco osmotin gene. Salt stress tolerance in transgenic olive plants was associated with the induction of the S assimilatory pathway, especially due to an increase in the activity of O-acetyl serine(thiol)lyase (OASTL) (Bashir et al, 2021).…”
Section: Role Of Osmotin In Abiotic Stress Tolerancementioning
confidence: 97%
“…In a recent report, Bashir et al (2021) demonstrated salt tolerance in transgenic olive (Olea europaea L.) plants over-expressing the tobacco osmotin gene. Salt stress tolerance in transgenic olive plants was associated with the induction of the S assimilatory pathway, especially due to an increase in the activity of O-acetyl serine(thiol)lyase (OASTL) (Bashir et al, 2021). Under cold treatment (15°C), the over-expression of N. tabacum osmotin gene improved seed germination rate, and the establishment and growth of seedlings in transgenic tomato (Solanum lycopersicum L.) (Patade et al, 2018).…”
Section: Role Of Osmotin In Abiotic Stress Tolerancementioning
confidence: 99%